Pengaruh Kualitas Pelayanan terhadap Kepuasan Wajib Pajak Kendaraan Bermotor di Kota Batu - M. Khoiru Rusydi; Fathoni - (Jurnal Aplikasi Manajemen, 2012)
The purposes of this research is to learn the influence of service quality which is consist of variable reliability, responsiveness, assurance, emphaty, and tangibles to satisfaction of society of taxpayer of motor vehicle. This research used survey method to 100 society of taxpayer of motor vehicle.samples were taken by purposive sampling, data source uses questionnaire as primary data, and document data as secondary data. The method of data analysis used is doubled regression. The result of this research shows that reliability, responsiveness, assurance, emphaty, and tangibles variable have effect on satisfaction of society of taxpayer of motor vehicle, while the rest less influenced by other variable which is not packed into a model. The analysis shows that together, independent variables have a significant simultaneous effect to Satisfaction of society of taxpayer of motor vehicle at Batu. Variable responsiveness has the most dominant influence to satisfaction of society of owner of motor vehicle, this conclusion is obtained from value of beta standardized coefficients.Keywords: Taxpayer of Motor Vehicle, Service of Quality, Satisfaction